2021
DOI: 10.3390/agronomy11101984
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Predator-In-First Strategy to Control Western Corn Rootworm Population in Maize Fields

Abstract: Western Corn Rootworm is a pest of maize that mostly damages roots. Many alternative strategies have been explored to control this species, with little or non-lasting success, and it remains a threat to maize production worldwide. Gaeolaelaps aculeifer, a soil-dwelling predatory mite that inhabits the first few centimeters of the soil, showed high predatory potential against WCR larvae in the laboratory. In this study, we explored the efficiency of G. aculeifer against WCR in more realistic contexts. First, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…This creates direct damage leading to yield loss (Riedell 1990 ; Sutter et al 1990 ; Spike and Tollefson 1991 ; Godfrey et al 1993 ; Gray et al 2009 ). Laboratory studies showed promising results when testing predatory soil mites against this pest; field experiments, however, gave mixed results (Prischmann-Voldseth et al 2011 ; Prischmann-Voldseth and Dashiell 2013 ; Pasquier et al 2021a , b ).…”
Section: Predator-prey Systemsmentioning
confidence: 99%
“…This creates direct damage leading to yield loss (Riedell 1990 ; Sutter et al 1990 ; Spike and Tollefson 1991 ; Godfrey et al 1993 ; Gray et al 2009 ). Laboratory studies showed promising results when testing predatory soil mites against this pest; field experiments, however, gave mixed results (Prischmann-Voldseth et al 2011 ; Prischmann-Voldseth and Dashiell 2013 ; Pasquier et al 2021a , b ).…”
Section: Predator-prey Systemsmentioning
confidence: 99%